Attrition of paracetamol and aspirin under bulk shear deformation. (24th March 2015) - Hare, C.; Ghadiri, M.
Abstract: Particles are frequently exposed to shear stresses during manufacturing, which leads to breakage. This is particularly relevant to weak active pharmaceutical ingredients and is prevalent in pharmaceutical and food industries. The attrition of paracetamol and aspirin caused by shear deformation at very low stresses is investigated here. The extent of breakage of these particles is related to the prevailing shear stresses and strains. In contrast to the expected trend, smaller particles exhibited increased breakage rates. At the onset of shearing at low stresses aspirin particles experienced slightly more breakage than the paracetamol, however prolonged shearing resulted in greater breakage of paracetamol. Breakage occurred initially through chipping with some fragmentation, particularly more noticeable for aspirin, with an increase in abrasion after extensive shear strain for paracetamol. Empirical breakage relationships are proposed and when combined with process stresses and strain analyses the extent of breakage occurring in process equipment can be estimated. Graphical abstract: Highlights: Breakage of paracetamol and aspirin established for given stress and strain. Empirically determined at low stresses (0.1–3.0 kPa). Aspirin breaks more easily at onset of shearing. Paracetamol more prone to breakage at increased stress or strain. Surprisingly no preferential breakage along cleavage planes.